Removal of dust artifacts in focal stack image sequences - Li, Chen; Zhou, Kun; Lin, Steve (2012 IEEE Conference on Computer Vision and Pattern Recognition (CVPR), 2012)
We propose a technique for removing the appearance of sensor dust in a focal stack image sequence captured with multiple focus settings. Our method is based on the key observation that sensor dust artifacts shift in image position with respect to focus setting, which allows scene information occluded by dust in one image to be inferred from other images in the focal stack. To deal with complications arising from differences in local defocus blur among the images, we analyze the relative blur among corresponding image regions in detecting and removing dust artifacts. Our results show improvements over the state-of-art technique for automatic removal of sensor dust.